Engaging frontline workers in policy development to support the implementation of measurement-based care: Lessons learned from a field-based workgroup - Singh, Rajinder Sonia; Landes, Sara J.; Resnick, Sandra G.; Abraham, Traci H.; Maieritsch, Kelly P.; Pollack, Stacey J.; Kirchner, JoAnn E. (Frontiers in Health Services, 2022)
Measurement-Based Care (MBC) is the use of patient-reported outcome measures repeatedly over the course of treatment to track progress and empower both providers and patients to collaboratively set goals and plan treatment. The Measurement-Based Care in Mental Health Initiative within the Department of Veterans Affairs' Office of Mental Health and Suicide Prevention partnered with the Post Traumatic Stress Disorder (PTSD) Mentoring Program to create an interdisciplinary field-based workgroup. The workgroup included psychologists, clinical social workers, and mental health counselors from PTSD Clinical Teams. The task of the workgroup was to create guidelines for best practice in delivery of MBC in PTSD Clinical Teams given anticipated policy requiring MBC to be used in PTSD Clinical Teams. Framed in the Strategic Action Field Framework for Policy Implementation Research, the current paper evaluates this hybrid top-down and bottom-up process of policy development. Major barriers included difficulty with the workgroup as an authentic bottom-up process, inability to reach the entire field (e.g., focus groups not widely attended by providers), and limited diversity in the workgroup. Facilitators included using consensus to make decisions, support provided to workgroup members by national operations partners, and collaboration and mutual respect among workgroup members. Workgroup members noted an equal, respectful partnership between operations partners and the workgroup; they reported feeling empowered and believed the viewpoints of the field were included in the guidelines. Further, due to the COVID-19 pandemic, the workgroup included more guidelines specific to telehealth into the guidelines. This hybrid model provides a process through which frontline workers can inform policy development and implementation.